2004
DOI: 10.1242/jcs.01083
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-mediated canal formation in primmorphs from the sponge Suberites domuncula involves the expression of a CD36 receptor-ligand system

Abstract: Sponges (Porifera), represent the phylogenetically oldest metazoan phylum still extant today. Recently, molecular biological studies provided compelling evidence that these animals share basic receptor/ligand systems, especially those involved in bodyplan formation and in immune recognition, with the higher metazoan phyla. An in vitro cell/organ-like culture system, the primmorphs, has been established that consists of proliferating and differentiating cells, but no canals of the aquiferous system. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…The SRB has been identified in most orders of insects (Diptera, Hymenoptera, Coleoptera, and Lepidoptera) (Hart and Wilcox 1993) as well as nematodes, sponges, and slime mold (Muller et al 2004). Many insect species have an SRB ortholog, the sensory neuron membrane protein (SNMP), on dendrites of the specialized neural cells in antennae involved in pheromone detection (Acton et al 1996;Nichols and Vogt 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The SRB has been identified in most orders of insects (Diptera, Hymenoptera, Coleoptera, and Lepidoptera) (Hart and Wilcox 1993) as well as nematodes, sponges, and slime mold (Muller et al 2004). Many insect species have an SRB ortholog, the sensory neuron membrane protein (SNMP), on dendrites of the specialized neural cells in antennae involved in pheromone detection (Acton et al 1996;Nichols and Vogt 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The elucidation of the molecular and cellular mechanism(s) by which sponges protect themselves against parasitic metazoans has begun only recently. It could be demonstrated that sponge-associated bacteria produce 2-methylthio-1,4-napthoquinone, a compound that suppresses the CD36/LIMPII signal transduction pathway that modulates angiogenesis (in vertebrates) and canal formation (in S. domuncula) (37).…”
mentioning
confidence: 99%
“…These NPs include shark cartilage, curcumin, the omega-3 and omega-6 fatty acids, green tea, licorice, quercetin, squalamine and vitamin D3 (Marwick 2001). Apart from shark cartilage (Cho and Kim 2002;Gingras et al 2003), some marine natural compounds from sponges (Zhou et al 2000;Shin et al 2001;Rodriguez-Nieto et al 2002) and sponge-associated bacteria (Müller et al 2004;Thakur et al 2005) have also been reported to possess anti-angiogenic potential, highlighting the importance of including NPs in the search for anti-angiogenic molecules.…”
Section: Anti-angiogenesismentioning
confidence: 99%